Reimagining the Cold War: Capitalist realism, anti-communism and nostalgia in twenty-first-century TV and streaming series. Issue 1 (1st March 2022) - Knewitz, Simone
This article analyses three contemporary TV and streaming series that reimagine the Cold War era of the 1980s in a nostalgic mode: the docudrama Chernobyl (2019), the science fiction series Stranger Things (2016‐present) and the spy thriller The Americans (2013‐18). It argues that these productions rely on nostalgia and retro aesthetics in the service of an anti-communist imaginary and what Mark Fisher has called 'capitalist realism': the perception that capitalism is the only viable system of economic and political organization and, more crucially, that a coherent alternative to it has become unimaginable in our current, allegedly post-ideological, historical moment. The series present us with a past in which the future was still open ‐ when there were still alternatives to the paths now being taken, which are now foreclosed. As these series depict all ideologies as anachronisms, their nostalgic mode serves to continually reaffirm the capitalist belief system and to symbolically annihilate any socialist or communist alternatives, yet, at the same time, also reflects resistance to the contemporary neo-liberal order.